2018
DOI: 10.1038/s41467-018-04821-5
|View full text |Cite
|
Sign up to set email alerts
|

A synthetic enzyme built from DNA flips 107 lipids per second in biological membranes

Abstract: Mimicking enzyme function and increasing performance of naturally evolved proteins is one of the most challenging and intriguing aims of nanoscience. Here, we employ DNA nanotechnology to design a synthetic enzyme that substantially outperforms its biological archetypes. Consisting of only eight strands, our DNA nanostructure spontaneously inserts into biological membranes by forming a toroidal pore that connects the membrane’s inner and outer leaflets. The membrane insertion catalyzes spontaneous transport of… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
144
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 110 publications
(147 citation statements)
references
References 46 publications
3
144
0
Order By: Relevance
“…It was recently shown that this concept can be used for construction of autonomous DNA‐based “robots” that can sort nanoparticle cargoes on their surface (Figure D) or biohybrid rotor–stator nanoengines that move along predefined tracks . This work gives rise to the hope that molecular machines made from DNA will one day be able to perform complex tasks, such as the controlled translocation of molecules across barriers, the evaluation of the molecular composition of cell surfaces for therapeutic purposes, or the assembly of tiny electrical and mechanical devices. Given that basic functions have been demonstrated in proof‐of‐concept studies, it seems reasonable that the next level of sophistication will be attainable by consequent implementation of molecular bottom‐up assembly and top‐down microengineering.…”
Section: Dna Origami Nanostructuresmentioning
confidence: 99%
“…It was recently shown that this concept can be used for construction of autonomous DNA‐based “robots” that can sort nanoparticle cargoes on their surface (Figure D) or biohybrid rotor–stator nanoengines that move along predefined tracks . This work gives rise to the hope that molecular machines made from DNA will one day be able to perform complex tasks, such as the controlled translocation of molecules across barriers, the evaluation of the molecular composition of cell surfaces for therapeutic purposes, or the assembly of tiny electrical and mechanical devices. Given that basic functions have been demonstrated in proof‐of‐concept studies, it seems reasonable that the next level of sophistication will be attainable by consequent implementation of molecular bottom‐up assembly and top‐down microengineering.…”
Section: Dna Origami Nanostructuresmentioning
confidence: 99%
“…Transportation of molecular cargos represents one of the most promising applications of dynamic DNA structures. For instance, Keyser et al demonstrated that a DNA nanostructure with cholesterol tags was able to dock into biological membranes, and effectively catalyze the transport of lipid molecules between the inner and outer leaflets, outperforming the corresponding biological archetypes by three orders of magnitude ( Figure a) . Numerous studies have proposed strategies to load, deliver, and release molecular drugs for gene silencing, immunostimulation, and photodynamic therapy using static DNA structures .…”
Section: Nanorobotic Systems For Molecular Cargo Transportationmentioning
confidence: 99%
“…a) A DNA nanostructure with cholesterol tags that scrambles lipid molecules between interior and outerior membranes at high speed. Reproduced with permission . Copyright 2018, Springer Nature.…”
Section: Nanorobotic Systems For Molecular Cargo Transportationmentioning
confidence: 99%
“…c A TiO 2 -CdS complex for H 2 production. Reproduced from Ma et al [128], with permission, copyright 2015, John Wiley and Sons synthetic scramblase built from DNA nanostructures [132]. As shown in Fig.…”
Section: Biomimetic Assembly Of Macromolecular Complexesmentioning
confidence: 99%